A Fool's Gold Christmas [compact disc, unabridged] - Mallery, Susan (Mallery, Susan. Fool's gold, 2012)
The unrelenting cheer in Fool's Gold, California, is bringing out the humbug in dancer Evie Stryker. She learned early on that Christmas miracles don't happen, at least not for her. And this year seems like no exception. An injury has forced her to return to the family fold, no matter that they're estranged. She won't add to the awkward scenario by being seduced by the bad-boy charms of her brother's best friend, the last man she should ever want to date.